Human cerebral organoids: cellular composition and subcellular morphological features - Mateos-Martínez, Patricia; Coronel, Raquel; Sachse, Martin; González-Sastre, Rosa; Maeso, Laura; Rodriguez, Maria Josefa; Terrón, María C.; López-Alonso, Victoria; Liste, Isabel (Frontiers in Cellular Neuroscience, 2024)
Introduction Human cerebral organoids (hCOs) derived from pluripotent stem cells are very promising for the study of neurodevelopment and the investigation of the healthy or diseased brain. To help establish hCOs as a powerful research model, it is essential to perform the morphological characterization of their cellular components in depth. Methods In this study, we analyzed the cell types consisting of hCOs after culturing for 45 days using immunofluorescence and reverse transcriptase qualitative polymerase chain reaction (RT-qPCR) assays. We also analyzed their subcellular morphological characteristics by transmission electron microscopy (TEM). Results Our results show the development of proliferative zones to be remarkably similar to those found in human brain development with cells having a polarized structure surrounding a central cavity with tight junctions and cilia. In addition, we describe the presence of immature and mature migrating neurons, astrocytes, oligodendrocyte precursor cells, and microglia-like cells. Discussion The ultrastructural characterization presented in this study provides valuable information on the structural development and morphology of the hCO, and this information is of general interest for future research on the mechanisms that alter the cell structure or function of hCOs.